2020
DOI: 10.1155/2020/3207345
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Fibrinogen/Albumin Ratio and Systemic Inflammation Response Index Predicts Survival in Resectable Gastric Cancer

Abstract: Aims. Predicting the prognosis of gastric cancer using tumour-node-metastasis (TNM) staging is difficult as patients with the same TNM stage exhibit different prognoses. Methods. This study investigated the prognostic value of the preoperative fibrinogen/albumin ratio (FAR)-systemic inflammation response index (SIRI) score in resectable gastric cancer (rGC). Results. Clinicopathological features of 231 rGC patients were analysed retrospectively. Patients were divided into three groups: FAR-SIRI score 2 (FAR≥0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…We included 14 published articles through systematic search, including 21 cohort studies, and a total of 6,035 cases (Table 1 ). [ 10 , 14 26 ] One article included three cohort studies, five articles included two cohort studies, and the remaining eight articles included one cohort study. This meta-analysis involved various malignancies, including pancreatic cancer, [ 10 ] gastric adenocarcinoma, [ 14 ] hepatocellular carcinoma, [ 15 ] esophageal squamous cell carcinoma, [ 16 ] nasopharyngeal carcinoma, [ 17 ] adenocarcinoma of the esophagogastric junction, [ 18 ] clear cell renal cell carcinoma, [ 19 ] pancreatic ductal adenocarcinoma, [ 20 ] non-small-cell lung cancer, [ 21 ] upper tract urothelial carcinoma, [ 22 ] metastatic pancreatic cancer, [ 23 , 25 ] breast cancer, [ 24 ] and resectable gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included 14 published articles through systematic search, including 21 cohort studies, and a total of 6,035 cases (Table 1 ). [ 10 , 14 26 ] One article included three cohort studies, five articles included two cohort studies, and the remaining eight articles included one cohort study. This meta-analysis involved various malignancies, including pancreatic cancer, [ 10 ] gastric adenocarcinoma, [ 14 ] hepatocellular carcinoma, [ 15 ] esophageal squamous cell carcinoma, [ 16 ] nasopharyngeal carcinoma, [ 17 ] adenocarcinoma of the esophagogastric junction, [ 18 ] clear cell renal cell carcinoma, [ 19 ] pancreatic ductal adenocarcinoma, [ 20 ] non-small-cell lung cancer, [ 21 ] upper tract urothelial carcinoma, [ 22 ] metastatic pancreatic cancer, [ 23 , 25 ] breast cancer, [ 24 ] and resectable gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…This meta-analysis involved various malignancies, including pancreatic cancer, [ 10 ] gastric adenocarcinoma, [ 14 ] hepatocellular carcinoma, [ 15 ] esophageal squamous cell carcinoma, [ 16 ] nasopharyngeal carcinoma, [ 17 ] adenocarcinoma of the esophagogastric junction, [ 18 ] clear cell renal cell carcinoma, [ 19 ] pancreatic ductal adenocarcinoma, [ 20 ] non-small-cell lung cancer, [ 21 ] upper tract urothelial carcinoma, [ 22 ] metastatic pancreatic cancer, [ 23 , 25 ] breast cancer, [ 24 ] and resectable gastric cancer. [ 26 ] The publication years were between 2016 and 2020, the sample capacity ranged from 76 to 542, and the cutoff of SIRI ranged from 0.54 × 10 9 to 2.3 × 10 9 . As for the quality assessment of included studies, the NOS score of 17 cohort studies was 8, one cohort study had score 7, and three studies had score 6.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported that plasma fibrinogen levels are positively correlated with many inflammation scores, such as the neutrophil/lymphocyte ratio, platelet/lymphocyte ratio and lymphocyte/monocyte ratio. 23,31 Fibrinogen can also induce the synthesis of interleukin 6 to promote tumor progression. 32 Albumin is the most abundant circulating protein in the plasma and is not only a nutritional indicator but can also be involved in the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Some studies have reported that the combination of fibrinogen and albumin can be used to predict the prognosis of cancer patients. 20,21 The baseline FAR was found to be an independent prognostic factor in patients with esophageal squamous cell carcinoma, 20 soft tissue sarcoma, 21 hepatocellular carcinoma, 22 gastric cancer, 23 and so on. In addition, researchers found that a high FAR was significantly associated with deeper tumor infiltration, lymph node metastasis and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“… 23 Therefore, we proposed using a novel marker, the FPR-PNI score, representing a combination of inflammation, coagulation function and nutritional status, to investigate its prognostic impact in patients with resectable gastric cancer. 24 …”
Section: Introductionmentioning
confidence: 99%